Problems of Ruler and Statehood in the Golden Horde Literature » - Khatip Minnegulov (Золотоордынское обозрение)
Already in ancient and medieval times, the Turks and their ancestors – Proto-Turks – established their own states and accumulated considerable political and administrative experience in the management and administration of their own countries. Their activities in this field was conditioned by the historical reality. They have also been displayed, in varying degrees, in the written literature, in particular: in runic inscriptions and the writings of Yusuf Balasaguni, Yugneki, Kul Gali and other authors. As is known, during two centuries of its existence, the Golden Horde left a deep mark in the statehood history and spiritual life of the peoples of Eurasia and even of the Northern Africa (Mamluk Egypt). Various problems of social and spiritual life are reflected in the preserved written literature of the Jochid ulus. Issues related to the ruler and his relationship with his subjects occupy an important place among these problems, as well as the problem of creating such a society, which would be reigned by “prosperity”, “happiness” and “justice”. Professor Kh.Yu. Minnegulov examines these questions by analyzing the works of such leading Turkish-Tatar writers and poets of the Golden Horde as: Rabguzi, Qutb, Khwarizmi, Mahmud Bulgari, Hisam Kyatib, Saif Sarayi, Ahmed Urgendzhi and others. The author points out that almost all the masters of the pen wanted the Lord being the ideal, perfect man (“Kamil Insan”) in every respect, especially fair, educated, morally mannered person. In their opinion, not the people but the sovereign should serve his subjects as a “shepherd” (“chuban”) and a “healer”. Some writings do not give preference to ordinary rulers, but to the reigning prophets (“Kyyssas al-Anbiya”, 1310; “Nahj al-Faradis”, 1358). In turn, in his poem “Jumjuma Sultan” (1369), the Sufi poet Hisam Kyatib even condemns and denies, to a certain extent, the “sultan’s power”. The writers urge the Golden Horde rulers to mostly listen to the views of scholars and religious leaders and remind them of the transience of life, implacability of death, as well as of the need to leave behind a “good name”.